Does self-employment increase the economic well-being of low-skilled workers? - Magnus Lofstrom (Institute for the Study of Labor (IZA), 2009)
Low-skilled workers do not fare well in today's skill intensive economy and their opportunities continue to diminish. Given that individuals in this challenging skill segment of the workforce are more likely to have poor experiences in the labor market, and hence incur greater public expenses, it is particularly important to seek and evaluate their labor market options. Utilizing data from the Survey of Income and Program Participation, this paper provides a comprehensive analysis of the economic returns to business ownership among low-skilled workers and addresses the essential question of whether self-employment is a good option for low-skilled individuals that policymakers might consider encouraging. The analysis reveal substantial differences in the role of self-employment among low-skilled workers across gender and nativity - women and immigrants are shown to be of particular importance both from the perspectives of trends and policy relevance. We find that although the returns to low-skilled self-employment among men are relatively high we find that wage/salary employment is a substantially more financially rewarding option for most women. These findings raise the question of why low-skilled women enter self-employment. Our business start-up results are consistent, but not conclusive, with lack of affordable child care options and limited labor market opportunities in the wage/salary sector as motivating native born women to enter self-employment. We do not find empirical evidence of similar constraints among immigrant women.
Keywords: J15; J16; J31; L26; 330; Self-employment; entrepreneurship; low-skill; women; immigrants; Ungelernte Arbeitskräfte; Selbstständige; Unternehmer; Unternehmensgründung; Lebensqualität; Migranten; Frauenerwerbstätigkeit; USA